Mediating effect of sequential memory on the relationship between visual-motor integration and self-care performance in young children with autism spectrum disorder - Lin, Ling-Yi; Chi, I-Jou; Sung, Yi-Shan (Frontiers in Psychology, 2022)
Objective Visual perception is a skill that contributes to the performance of self-care and important development tasks in early childhood. The relationship between self-care and visual perception is especially significant for young children with autism spectrum disorder (ASD), who have been described as visual learners. However, this relationship is not clearly understood among young children with ASD. We investigated the role of motor-free visual perception on the relationship between self-care and visual-motor integration in young children with ASD. Methods A sample of 66 children with ASD aged 48 to 83 months were recruited. Measurements included the Assessment of Motor and Process Skills, the Developmental Test of Visual Perception—Third Edition, and Test of Visual-Perceptual Skills—Third Edition. Results The results indicated that self-care performance had significant positive correlations with visual-motor integration, visual discrimination, visual memory, visual spatial relationships, and visual sequential memory. Of these, visual sequential memory and visual spatial relationships were the main factors related to self-care performance. Sequential memory was a mediator of the relationship between visual-motor integration and self-care performance. Conclusion This study establishes a deeper understanding of self-care and motor-free visual perception among young children with ASD. Understanding the relationship between visual perception and self-care in young children with ASD may aid professionals in providing self-care interventions for this population.